A 42.15–68.35 dBΩ tunable gain transimpedance amplifier using 0.18‐μm CMOS process. Issue 4 (April 2015) - Chang, Yu‐Hsin; Chiang, Yen‐Chung; Yang, Ching‐Yuan
ABSTRACT This letter proposes a transimpedance amplifier with a tunable gain fabricated in the 0.18‐μm CMOS process. The tunable gain range is from 42.15 to 68.35 dBΩ with a 2.88–3.52 GHz bandwidth, and its group delay is around 200 ps. With 2.5 Gb/s, 215−1, 223−1, and 231−1 pseudorandom bit sequence inputs, the corresponding recovered clock jitters are 7.72, 7.83, and 8.3 ps, respectively. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:830–832, 2015